Genetic diversity of indigenous catfish from Indonesia based on mitochondrial Cytochrome Oxidase Subunit II gene - Vista Budiariati; Trini Susmiati; Siti Munawaroh; Rachmawati Cahyaningtyas Arie Putri; Rini Widayanti Widayanti (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Budiariati V, Susmiati T, Waroh S, Putri RCA, Widayanti R. 2021. Genetic diversity of indigenous catfish from Indonesia based on mitochondrial Cytochrome Oxidase Subunit II gene. Biodiversitas 22: 593-600. Catfish is one of the most demanding fish in Indonesia and served in a variety of traditional culinary. Due to their identical morphology and close relation between species in the order of Siluriformes, it is quite tricky to distinguish the species. This can be a threat to develop catfish production in Indonesia since there is a wide variety of catfish species in this mega biodiversity country. The study aimed to analyze the genetic diversity of Indonesian indigenous catfish especially those known as Baung fish by local people based on COII gene. The study also aimed to determine the phylogenetic relationship between the samples and compare them with the GenBank data. A total of 24 samples used in this study from 8 different rivers from 3 different islands and two samples were collected from coastal areas. The study results showed that there is genetic diversity of the Indonesian indigenous catfish based on COII gene. The sequences among 24 samples showed that from 691 nucleotides of COII gene, there were very subtle nucleotides differences of samples that originated from Bojonegoro, Magelang, and samples collected from Baru Beach, Yogyakarta. Based on COII amino acid sequences, 6 polymorphic amino acid sites were on-site number 64, 115, 123, 129, 144, and 165. The samples encoded LLB1 and LPB1 from Baru Beach, Yogyakarta, showed highest different amino acids in the six sites. Samples from the river of Central Java, Sumatra, and Kalimantan belonged to Bagridae family and consist of two different species Hemibagrus sp. and Mystus sp while samples from East Java belonged to Pangasiidae family. The Samples from coastal belonged to Ariidae family.